The Influence Of Profitability, Capital Structure, And Company Growth On Company Value With Dividend Policy As A Moderating Variable In Insurance Companies Listed On The IDX From 2020 To 2024 - Sheni Faradhiba Yusuf; Muslimin; Nindytia Puspitasari Dalimunthe (Cita konsultindo, 2026)
This study aims to analyze the influence of profitability, capital structure, and company growth on firm value, with dividend policy as a moderating variable in insurance companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. Profitability is measured by Return on Assets (ROA), capital structure by Debt to Equity Ratio (DER), company growth by Growth Assets Ratio (GR), dividend policy by Dividend Payout Ratio (DPR), and firm value by Price to Book Value (PBV). The research sample consists of 21 insurance companies selected using the purposive sampling method. The analysis method employed is panel data regression, with the Random Effect Model (REM) identified as the most suitable model. The results indicate that profitability, capital structure, and company growth partially have no significant effect on firm value. Furthermore, dividend policy is not proven to moderate the influence of profitability, capital structure, or company growth on firm value. The low Adjusted R-squared value indicates that the independent variables in this study are insufficient to explain variations in firm value within the insurance sector during the observation period.